MOTIVASI MENJADI HOST COUCHSURFING DI INDONESIA - Deskanti, Rozzana; Mahadian, Adi Bayu (Jurnal IPTA (Industri Perjalanan Wisata), 2019)
Being a host is part of a new tourism activity in Indonesia known as free hospitality, the activity has a great potential but need encouragement to the actors. In the digital era new tourism actors are spread and connected via the internet, couchsurfing is one of the social media that is present in the development of tourism communication and as a liaison between actors of activities, encouragement is needed to motivate tourism growth in this sector. This study aims to know the highest level of motivation and motivator factors that can be used for government policy making. Motivation is one of the driving factors that influences a person to do something that is intended. This study uses descriptive quantitative methods with one variable. The independent variable in this study is Motivation to become a Couchsurfing host. The analysis technique used is descriptive analysis technique. This research was conducted by distributing questionnaires to 100 respondents by combining two nonprobability sampling techniques, namely; purposive sampling, and quota sampling. The results of this study state that the motivation to host Couchsurfing in Indonesia is in the high category with an amount of 75.1% and the highest motivation is in the cultural factor of 94%. The conclusion of this study is that actors want to carry out cultural exchanges, by being a host, local residents can use their knowledge of the culture and local area to attract tourist visits.